2022
DOI: 10.3390/jcm11175001
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Lung Ultrasound in COVID-19 Critically Ill Patients: A Narrative Review

Abstract: Lung ultrasound (LUS) has a relatively recent democratization due to the better availability and training of physicians, especially in intensive care units. LUS is a relatively cheap and easy-to-learn and -use bedside technique that evaluates pulmonary morphology when using simple algorithms. During the global COVID-19 pandemic, LUS was found to be an accurate tool to quickly diagnose, triage and monitor patients with COVID-19 pneumonia. This paper aims to provide a comprehensive review of LUS use during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Physicians brought the LUS from the medical service to outpatient settings using portable devices [ 78 , 79 ]. The LUS was found to be an accurate tool to quickly diagnose, triage, and monitor patients with COVID-19 pneumonia [ 80 ]. In an Italian survey proposed to anesthesiologists and intensive care physicians after the first wave of the COVID-19 pandemic, the results showed that the LUS was extensively used during the first phase of the pandemic, and then, its adoption increased further [ 81 ].…”
Section: Lung Ultrasound In Common Clinical Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians brought the LUS from the medical service to outpatient settings using portable devices [ 78 , 79 ]. The LUS was found to be an accurate tool to quickly diagnose, triage, and monitor patients with COVID-19 pneumonia [ 80 ]. In an Italian survey proposed to anesthesiologists and intensive care physicians after the first wave of the COVID-19 pandemic, the results showed that the LUS was extensively used during the first phase of the pandemic, and then, its adoption increased further [ 81 ].…”
Section: Lung Ultrasound In Common Clinical Scenariosmentioning
confidence: 99%
“…Despite the good association described, in patients with other comorbidities (e.g., acute cardiogenic pulmonary edema, chronic interstitial lung disease, etc.) presenting with acute respiratory failure, the interstitial syndrome identified by LUS could be difficult to be attributed to COVID-19 pneumonia rather than to a decompensated previous illness [ 80 ]. A recently published systematic review including 66 articles with a pool of 4687 patients observed that the most frequent ultrasound findings in COVID-19 patients were B-lines and pleural abnormalities and confirmed the association between a high LUS score at admission and unfavourable outcomes [ 84 , 85 , 86 ].…”
Section: Lung Ultrasound In Common Clinical Scenariosmentioning
confidence: 99%
“…For unstable patients, thoracic ultrasound has been considered as a useful adjunct especially in the critical care setting, but the diagnosis cannot always be made with certainty due to artifacts arising from underlying lung parenchymal changes. 32 Computed tomography (CT-chest) is often performed in these patients with PTX and COVID-19 as it not only provides invaluable information about extent of PTX and associated PTM or SCE, but also helps to decide management. 10,31 With increasing evidence of coexistence of PTX or thromboembolic disease in COVID-19 patients, the majority of patients with moderate to severe disease undergo CT-chest examination early in their treatment course, especially if high risk to require ventilatory support, due to technical challenges in transporting these patients for scanning purposes.…”
Section: Imagingmentioning
confidence: 99%
“…For unstable patients, thoracic ultrasound has been considered as a useful adjunct especially in the critical care setting, but the diagnosis cannot always be made with certainty due to artifacts arising from underlying lung parenchymal changes. 32…”
Section: Pneumothorax In Covid-19 Patientsmentioning
confidence: 99%
“…If proven to accurately predict clinical deterioration, LUS findings could be integrated with clinical findings at the time of ED presentation, to triage patients to either outpatient management (low-risk features), ward admission (moderate-risk features) or intensive care unit (ICU) admission (high-risk features). 17 This could potentially impact patient outcomes, resource allocation and departmental flow, particularly in times of crisis and overcrowding.…”
Section: Introductionmentioning
confidence: 99%